Early identification of cardiac ATTR amyloidosis: a clinical case - A. A. Vedernikov; E. M. Mezhonov; N. Е. Shirokov; V. A. Balina; O. M. Reitblat; D. V. Teffenberg; S. V. Shalaev (Столичная издательская компания, 2024)
Progress in instrumental diagnostics, as well as increased awareness among doctors about rare diseases, is steadily leading to an increased number of patients diagnosed with cardiac amyloidosis. Regardless of amyloid formation route, cardiac damage is the main cause of mortality in systemic amyloidosis. The article presents a unique clinical observation of hereditary transthyretin (ATTR) amyloidosis mixed phenotype detection during skeletal scintigraphy. In the patient with severe shortness of breath, based on the results of radiological research, an oncological process in the lungs was suspected. The patient underwent skeletal scintigraphy to exclude metastatic lesions, during which a scintigraphy pattern characteristic of ATTR amyloidosis (Grade 3) was revealed. Subsequently, the oncological diagnosis was removed. An independent disease of hematopoietic system was excluded, and mutation in TTR gene was additionally confirmed. This clinical case illustrates the possibility of making a diagnosis of cardiac amyloidosis without resorting to myocardial biopsy, when the patient still has slight limitations in physical activity (NYHA class II) and there is no late gadolinium enhancement on magnetic resonance imaging.